Pathophysiology [ concepts of altered health states - Porth (Philadelphia: Lippincott Williams & Wilkins, 2009)
Minimum system requirements: IBM PC; CD-ROM drive; Windows
To accompany textbook titled "Pathophysiology : concepts of altered health states / Carol Mattson Porth, Glenn Matfin"
FMHS
Keywords: Disease -- -- Nurses' Instruction; Pathology -- -- Nurses' Instruction; Physiology -- -- Nurses' Instruction; Nursing; Physiology, Pathological